The causes and consequences of the Ukraine war A lecture by John J. Mearsheimer - The Robert Schuman Centre for Advanced Studies (2022)
Professor John J. Mearsheimer will discuss the current Russian invasion on Ukraine whilst exploring the potential causes and consequences of the crisis. In this lecture, Prof. Mearsheimer will aim to focus on both the origins of the war in Ukraine and some of its most important consequences. He will argue that the crisis is largely the result of the West’s efforts to turn Ukraine into a Western bulwark on Russia’s border. Russian leaders viewed that outcome as an existential threat that had to be thwarted. While Vladimir Putin is certainly responsible for invading Ukraine and for Russia’s conduct in the war, Prof. Mearsheimer states that he does not believe he is an expansionist bent on creating a greater Russia. Regarding the war’s consequences, the greatest danger is that the war will go on for months if not years, and that either NATO will get directly involved in the fighting or nuclear weapons will be used — or both. Furthermore, enormous damage has already been inflicted on Ukraine. A prolonged war is likely to wreak even more devastation on Ukraine. Prof. John J. Mearsheimer is the R. Wendell Harrison Distinguished Service Professor in the Political Science Department at the University of Chicago. Disclaimer – The views and opinions expressed in this video are those of the speakers or authors in their personal capacity and do not necessarily reflect the official position of the Robert Schuman Centre or the European University Institute. Learn more about the Schuman Centre: https://bit.ly/3NEAzRl